THE INFLUENCE OF AMIRKAN GYMNASTICS (ANTI DYSMENORRHEA FOR ADOLESCENTS THROUGH MOVEMENT) ON REDUCING DYSMENORRHEA PAIN LEVELS - Rita Sopiatun; Ni Putu Dian Ayu Anggraeni; Arista Kusuma Wardani (Universitas Karya Husada Semarang, 2025)
Menstrual pain has a significant impact on teenage girls as it disrupts their daily activities. Dysmenorrhea that often occurs in adolescents is primary dysmenorrhea, which is menstrual pain that occurs after the first few years of menstruation. One of the exercises that can be used to alleviate dysmenorrhea is gymnastics.Research Objective: To determine the effect of AMIRKAN exercise on the reduction of menstrual pain in junior high school students in Labuapi District. This type of research is pre-experimental with a one group pretest-posttest design. The population in this study consists of all seventh and eighth-grade female students from each school: SMPN 1 Labuapi with 134 students, SMPN 2 Labuapi with 134 students, and SMPN 3 Labuapi with 137 students. The sampling technique was based on calculations using Proportional Random Sampling according to inclusion and exclusion criteria, totaling 100 students. Data analysis used the chi-square test. The research shows that the Amirkan exercise (anti-dysmenorrhea for adolescents through movement) has an effect on reducing dysmenorrhea pain levels among seventh and eighth-grade female students at junior high schools in Labuapi District. The Amirkan exercise intervention, performed regularly 2-3 days before menstruation, can stretch the abdominal and pelvic muscles, making it a potential effort to reduce menstrual pain.